Feasibility of trauma-focused cognitive behavioural therapy for patients with PTSD and psychosis - Buhmann, Caecilie B.; Mortensen, Erik Lykke; Graebe, Frida Lau; Larsen, Sarah K.; Harder, Susanne; Arnfred, Sidse; Austin, Stephen F. (Frontiers in Psychiatry, 2024)
Studies have shown a high prevalence of trauma and PTSD among patients with severe mental illness, but relatively only few studies have examined the outcomes of PTSD treatment for this patient group. The aim of this case-series was to assess the feasibility of a Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) intervention for PTSD in people with psychosis. The study examined the possibilities and obstacles when treating this population within clinical settings. Patients were selected from four community mental health centers and were screened for traumatic experiences and symptoms of PTSD. A small group of eligible participants (n=7) received manualized TF-CBT adapted for patients with psychosis. Experienced therapists received training and supervision in the intervention. Symptoms of PTSD and psychosis were assessed at baseline and post-treatment along with quality of life, level of functioning, alliance, life events, engagement, suicidal ideation and adverse events. Treatment fidelity and the different combinations of treatment modules were monitored in regard to implementation. Three cases were selected as illustrative of the different treatment courses when implementing the TF-CBT intervention within this population. Detailed case descriptions were based on quantitative ratings and the therapists’ experiences with the therapy. Results from the case series highlighted issues regarding toleration of treatment, large variation in psychopathology and the task of matching treatment needs with appropriate and therapeutic techniques. The complexity of the patient group may affect treatment and clinical research studies. Lessons learned from this case series can contribute to the future development implementation and evaluation of trauma treatment for patients with psychosis.